Analyzing Grammatical Range And Accuracy In The Speaking Skills Of Street Vendors In Tourism Area - Emiliana, Emiliana; Marzuki, M. Junaidi; Surayya, Siti Ayu; Husnu, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the level of extended grammatical range and accuracy in the speaking skills of street vendors in the tourism area in Kuta Mandalika Beach, Central Lombok. The research involved 9 people of street vendors. This study employed qualitative research methods, using interviews with the IELTS rubric descriptor to assess the street vendors' grammatical range and accuracy in speaking skills. The study's findings indicate that street vendors in the Mandalika tourism area have varying proficiency levels in English grammar and accuracy, with most participants scoring between 4 and 6 bands on the IELTS rubric. The study results showed that the participants' mean band score was approximately 4.44, indicating a